High Prevalence of β-lactamase and Plasmid-Mediated Quinolone Resistance Genes in Extended-Spectrum Cephalosporin-Resistant Escherichia coli from Dogs in Shaanxi, China - Liu, Xiaoqiang; Liu, Haixia; Li, Yinqian; Hao, Caiju (Frontiers in Microbiology, 2016)
Objective: The aim of this study was to investigate the occurrence and molecular characterization of extended-spectrum β-lactamases (ESBL), plasmid-mediated AmpC β-lactamase (pAmpC) and carbapenemases as well as plasmid-mediated quinolone-resistant (PMQR) among extended-spectrum cephalosporin-resistant (ESC-R) Escherichia coli from dogs in Shaanxi province in China. Methods: A total of 40 ESC-R Escherichia coli selected from 165 Extraintestinal pathogenic E. coli (ExPEC) isolated from dogs were screened and characterized for the genes encoding for the ESBLs, pAmpC, carbapenemases and PMQR genes by PCR and sequencing. Phylogenetic groups, virulence gene profiles and multilocus sequence typing (MLST) were used to investigate the genetic background of the ESC-R E. coli isolates. Results: Among 40 ESC-R E. coli, the predominant β-lactamase gene was blaCTX-Ms (n=35), and followed by blaTEM-1 (n=31), blaSHV-12 (n=14), blaOXA-48 (n=8), blaTEM-30 (n=4), blaCMY-2 (n=3) and blaDHA-1 (n=2). The most common specific blaCTX-M gene subtype was blaCTX-M-15 (n=31), and followed by blaCTX-M-123 (n=14), blaCTX-M-1 (n=10), blaCTX-M-14 (n=10) and blaCTX-M-9 (n=7). PMQR genes were detected in 32 (80%) isolates, and the predominant PMQR gene was aac(6')-Ib-cr (n=26), followed by qnrS (n=12), qnrD (n=9), qnrB (n=8), qepA (n=4), and all PMQR genes were detected in co-existence with β-lactamase genes. traT (n=34) and fimH (n=32) were the most prevalent virulence genes, and virulence genes fimH, iutA, fyuA, malX, iha and sat were more prevalent in phylogenetic group B2. The 40 ESC-R isolates analyzed were assigned to 22 sequence types (STs), and the clonal lineages ST131 (n=10) and ST10 (n=9) were the predominant STs. Conclusion: High prevalence of β-lantamases and PMQR genes were detected among ESC-R E. coli from companion animals. This is also the first description of the co-existence of six β-lantamase genes and five PMQR genes in one E. coli isolate. Moreover, ten ST131 clones harboring CTX-M-15 were detected.